The Impact of Reproductive Health Legislation on Family Planning Clinic Services in Texas - White, Kari (Am J Public Health, 2015)
We examined the impact of legislation in Texas that dramatically cut and restricted participation in the state’s family planning program in 2011 using surveys and interviews with leaders at organizations that received family planning funding. Overall, 25% of family planning clinics in Texas closed. In 2011, 71% of organizations widely offered long-acting reversible contraception; in 2012–2013, only 46% did so. Organizations served 54% fewer clients than they had in the previous period. Specialized family planning providers, which were the targets of the legislation, experienced the largest reductions in services, but other agencies were also adversely affected. The Texas experience provides valuable insight into the potential effects that legislation proposed in other states may have on low-income women’s access to family planning services.